2009
DOI: 10.1080/00220380802663575
|View full text |Cite
|
Sign up to set email alerts
|

Product Market Competition and Productivity in the Indian Manufacturing Industry

Abstract: The effects of product market competition on the growth rates of productivity of firms in the Indian manufacturing sector are examined for the decade since the economic reform in 1991. This study improves on the construction of variables that capture the extent of product market competition. Empirical results indicate that the smaller is the market share of a firm, the higher is the productivity growth of the firm, and this effect is more prominent in a less concentrated market.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 21 publications
(22 reference statements)
0
13
0
3
Order By: Relevance
“…The non-frontier parametric approach is known as the production function approach and the frontier non-parametric approach is popularly known as the growth accounting approach. Due to certain limitations, such as the assumption of constant returns to scale and perfect market conditions, the semi-parametric approach, such as the Levinsohn–Petrin (L-P) approach, has become popular over the years to estimate TFP (Blalock & Gertler, 2004; Coricelli, Driffield, Pal & Rolland, 2012; Ghosh, 2009; Kato, 2009; Sharma, 2014; Vial, 2006). Although the literature on the estimation of productivity is quite developed (see Balakrishnan & Pushpangadan, 1998; Beveren, 2012; Bontemps, Robin & Berg, 2000; Good, Nadiri & Sickles, 1996), studies on firm-specific determinants of productivity are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The non-frontier parametric approach is known as the production function approach and the frontier non-parametric approach is popularly known as the growth accounting approach. Due to certain limitations, such as the assumption of constant returns to scale and perfect market conditions, the semi-parametric approach, such as the Levinsohn–Petrin (L-P) approach, has become popular over the years to estimate TFP (Blalock & Gertler, 2004; Coricelli, Driffield, Pal & Rolland, 2012; Ghosh, 2009; Kato, 2009; Sharma, 2014; Vial, 2006). Although the literature on the estimation of productivity is quite developed (see Balakrishnan & Pushpangadan, 1998; Beveren, 2012; Bontemps, Robin & Berg, 2000; Good, Nadiri & Sickles, 1996), studies on firm-specific determinants of productivity are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Bas and Berthou (2011) and Ahsan (2013) find that firms that are more creditworthy and which are in industries that are more oriented toward importing foreign technology and different quality intermediate inputs, experience greater improvements in productivity following trade liberalization. Studies such as Balakrishnan et al (2006), Kato (2009), Loecker et al (2012, Goldberg et al (2010a) also find greater benefits of trade liberalization for those Indian manufacturing firms which continuously diversify their production. Goldberg et al (2010b), Kathuria (2002), Parameswaran (2010) find a positive and significant role of FDI orientation and R&D intensity in realizing the benefits of trade liberalization.…”
Section: Literature Reviewmentioning
confidence: 94%
“…A number of studies based on firm-level data (Krishna and Mitra [8]; Topalova [9]; Sivadasan [10]; Topalova and Khandelwal [11]) have observed that lowering of tariffs has led to faster productivity growth. Studies (Ray [12]; Siddharthan and Lal [13]; Goldar et al [14]; Banga [15]; Kato [16]) have also shown that import of disembodied technology, Research and Development (R & D) intensity and availability of wider varieties of higher quality imported inputs have favourable impact on productivity growth of Indian firms. However, Balakrishnan and Suresh Babu [17]; Srivastava [18] and Balakrishnan et al [19] could not find evidences of a widespread increase in the rate of productivity growth across all sectors.…”
Section: Review Of Studies On Technical Efficiency In An Era Of Economentioning
confidence: 99%